Effects of mavacamten on cardiac biomarkers in nonobstructive hypertrophic cardiomyopathy: insights from the ODYSSEY-HCM trial - Desai, Milind; Olivotto, Iacopo; Abraham, Theodore; Nissen, Steven E.; Garcia-Pavia, Pablo; Lopes, Renato D.; Elliott, Perry M.; Fernandes, Fabio; de Barros Correia, Edileide; Barriales-Villa, Roberto; Zorio, Esther; Arad, Michael; et al. (Journal of the American College of Cardiology, 2025)
Background - No therapy is approved for patients with symptomatic nonobstructive hypertrophic cardiomyopathy (nHCM). The ODYSSEY-HCM (A Study of Mavacamten in Non-Obstructive Hypertrophic Cardiomyopathy [ODYSSEY-HCM]; NCT05582395) trial, the largest to date in patients with hypertrophic cardiomyopathy (HCM), evaluating the efficacy of mavacamten in symptomatic adults with nHCM, did not demonstrate improvements in its primary endpoints (functional capacity and patient-reported health status). - Objectives - The current exploratory analysis from the ODYSSEY-HCM trial reports the associations between: 1) baseline biomarkers (N-terminal pro-B-type natriuretic peptide [NT-proBNP] and high-sensitivity cardiac troponin I [cTnI]) with clinical, exercise, and echocardiographic characteristics; and 2) comparing changes in these biomarkers from baseline to week 48 between mavacamten and placebo groups. - Methods - Symptomatic nHCM patients were randomized to placebo or mavacamten (starting at 5 mg/d, with titration ranging from 1 to 15 mg, based on left ventricular [LV] ejection fraction). Along with clinical and echocardiographic parameters, NT-proBNP and hs-cTnI were measured for changes from baseline to week 48. - Results - Among 580 randomized patients (mean age 56 ± 15 years, 266 [45.9%] women), baseline biomarkers were elevated with median NT-proBNP 917.5 ng/L (IQR: 463-1,725 ng/L) and hs-cTnI of 29.1 ng/L (IQR: 14.4-91.7 ng/L). On multivariable analysis, female sex, body mass index, NYHA functional class, maximal LV wall thickness, left atrial volume index, and E/e’ were associated with higher baseline NT-proBNP. Only younger age and LV mass index were associated with higher baseline hs-cTnI level. At week 48, the mavacamten group had a 58% reduction in NT-proBNP (geometric mean ratio: 0.42; 95% CI: 0.37-0.47; P < 0.001) and a 51% reduction in hs-cTnI (geometric mean ratio: 0.49; 95% CI: 0.45-0.53; P < 0.001). No significant change in either biomarker was seen in the placebo group. These reductions occurred early and were maintained through week 48. - Conclusions - Treatment with mavacamten for 48 weeks in nHCM patients was associated with marked biomarker improvements compared with placebo. Whether these changes translate into longer-term adaptive remodeling and improvements in patient-reported health status, exercise capacity, and outcomes remain to be ascertained. (A Study of Mavacamten in Non-Obstructive Hypertrophic Cardiomyopathy [ODYSSEY-HCM]; NCT05582395)
Online verfügbar: 27. August 2025, Artikelversion: 8. Dezember 2025
Gesehen am 20.02.2026